Pengaruh Reward, Punishment Dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi Kasus pada Hotel Wyndham Sundancer Resort Lombok) - Elsie Az Zaahra; Budi Wahono; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of reward, punishment and organizational commitment on employee performance at the Wyndham Sundancer Resort Lombok. The location of this research was conducted on employees who work at the Wyndham Sundancer Resort Lombok. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to employees who work at the Wyndham Sundancer Resort Lombok, which were selected by purposive sampling. Determination of the number of samples using the Slovin formula and the results obtained were 125 respondents. Data were analyzed using multiple linear regression and determination test. Based on the results of data analysis, the results of the F test indicate that reward, punishment and organizational commitment simultaneously have a significant and positive effect on the performance of the employees of the Wyndham Sundancer Resort Lombok Hotel. Furthermore, the results of the t test show that reward, punishment and organizational commitment have a significant and partially positive effect on the performance of the employees of the Wyndham Sundancer Resort Lombok Hotel. The results of the determination test show that the percentage is 82%, where employee performance is able to be influenced by reward, punishment and organizational commitment. Keywords: Employee Performance, Reward, Punishment, Organizational Commitment